Factors Influencing Consumers' Attitudes and Purchase Intentions of E-Deals - Cheah, Isaac; Phau, Ian; Liang, Johan (Emerald Group Publishing Limited, 2014)
Purpose - This paper identifies the key antecedents of attitude towards e-deals and factors influencing purchase intention of e-deals. Specifically, perceived value and price consciousness will be tested as antecedents of attitudes towards e-deals. Attitudes towards e-deals, subjective norms, and perceived behavioural control are proposed to have strong influences upon purchase intention. The theory of planned behaviour provides the theoretical underpinning of the conceptual framework. Design/methodology/approach – Data were collected through convenience sampling. Overall, 611 valid responses of 780 distributed surveys were collected. Only 426 e-deals users were analysed by using structural equation modelling (SEM) to test the hypotheses. Findings - It is found that perceived value is a strong predictor of attitudes towards e-deals. Another finding also indicates that attitudes towards e-deals and normative influence positively affect consumers’ purchase intention towards e-deals. Practical Implications - Practitioners are advised to integrate social media (e.g. Facebook or Twitter) and online communities to approach the “leader” to influence new potential consumers to purchase e-deals. It is also important to maintain the good value of e-deals and emphasize the huge benefits of using e-deals to persuade consumers to purchase it. Originality/value – The originality of this study lies in extending the Theory of Planned Behaviour and Social Cognitive Theory as a robust measurement to investigate online shopping behaviour in the context of e-deals.